Psychological characteristics of HIV-infected patients - N. N. Muryvanova; V. I. Gorbunov; T. N. Tkachenko; Yu. I. Bulan’kov; I. M. Ulukin (Журнал инфектологии)
The purpose of the study: the study of individual psychological characteristics of HIV-infected people. Materials and methods: we used the hospital anxiety scale and depression HADS, depression scale Beck and Zung. The results of the study: According to the scale HADS subclinical forms of anxiety are more common in women (31,5±2,65%) than men (12,5±1,48 %), and, at the age of 20-29 years. Clinically evident anxiety occurs more often in women (19±1,34%) than men (14,5±2,1 %) in the age – men – 20–29 years, while for women 20–24. Subclinical (18±1,34%) and clinical (9±0,68%) forms of depression have also been noted in the female population in the age 3,8±0,32% of men and 14,1±1,21% in women. On a scale of Beck expressed signs of depression found in 34,8±2,4% of men aged 25–29 years and 43±2,83% of women aged 20–24. Conclusion: 1. Our studies showed the presence of depressive and anxiety symptoms in a significant number of the surveyed HIV – infected. 2. In the analysis of different age and sex groups of HIVinfected patients, found that anxiety and depression more likely in women in the age group 20-29 years. 3. The obtained results can be used to develop methods of prevention of mental disorders.